Visual dialog system - Luong, Hien Nga (Nanyang Technological University, 2024)
In this era of Artificial Intelligence, Large Language Models (LLMs) have emerged as powerful tools, facilitating the revolution of natural language understanding and generation tasks across different domains. Many innovations such as OpenAI’s Generative Pretrained Transformer (GPT) series have proven their outstanding ability to comprehend and generate coherent text. The continuous evolution of Artificial Intelligence has led to advancement beyond linguistic abilities, enabling integration of multimodal functionalities.